DAMPAK PELAKSANAAN ACFTA (ASEAN-CHINA FREE TRADE AGREEMENT) PADA FDI EKTRA-REGIONAL DI INDONESIA - Amalia Astatiani (Jurnal Ilmiah Global Education, 2023)
The era of globalization encourages countries to integrate with other countries to fulfil domestic needs at lower prices and encourages the export of domestic products. When the countries conclude the Economic integration, besides of effect of the increment in international trade, there is also the effect of increasing FDI inflows which are called investment creation, which is the increment of FDI from extra-regional countries. Since Indonesia ratified ACFTA and the tariff between Indonesia and China became 0 tariffs in 2010, it raises questions about whether Indonesia had the investment creation from economic integration with China and what factors have influenced FDI flows in Indonesia since the ACFTA. This study attempts to answer this question using descriptive analysis and an econometric approach. The econometric approach in this study uses the gravity method by including panel data from 91 countries over a period of 13 years. The econometric approach gives the result that extra-regional countries have a significant negative effect on FDI inflows in Indonesia which makes Indonesia still needs to implement policies to attract FDI inflows from extra-regional.